Are endurance runners at higher risk of depression? Screening for depression and risk factors - Scheer, Volker; Valero, David; Thuany, Mabliny; Knechtle, Beat; Viljoen, Carel; Ruescas Escolano, Esther; Valero Burgos, Encarna (International Journal of Sports Medicine, 2025)
Depression is an important public health issue. In the general adult population, about 6.7% are affected. Little data are available about endurance runners. We conducted a prospective survey study screening for depression using the Patient Health Questionnaire and investigating potential associated risk factors in endurance runners (≥ 21.1–42.2 km) and ultraendurance runners (≥ 42.2 km). Statistical analysis included descriptive statistics, predictive techniques, and regression analysis. A total of n = 601 runners participated (female n=222 and male n=379; mean age [SD]: 42.8 years [± 10.1]). Overall, 11.3% screened positive for major depression, particularly female runners compared to male runners (p=0.002) and endurance runners compared to ultraendurance runners (p=0.023). No significant differences were observed among performance levels (elite vs. nonelite). Mild depression was observed in 21.6% of runners. Factors associated with a higher risk for screening for major depression included age (p<0.001), particularly runners under the age of 28 years, previous self-reported history of depression (p<0.001), more frequent weekly workouts (4–5/wk; p=0.021), weeks lost to injury (p=0.022), and female sex (p=0.025). A third of endurance and ultraendurance runners screened positive for depression, highlighting the importance of creating awareness for mental health issues and potential screening for athletes and providing access to appropriate support services and education.
Keywords: mental healh; ultramarathon; marathon; endurance sports; risk factors